Unsupervised type III polygraphy in children undergoing adenotonsillectomy: a technical and economic report - Iury Lima Veloso; Camila de Castro Corrêa; José Vicente Tagliarini; Silke Anna Theresa Weber (Sleep Science)
Objective: To evaluate the economic and technical viability of the sleep study (type III) in children with adenotonsilar hypertrophy. Methods: 141 children were submitted to sleep study (type III), aged between three and 11, all with symptoms of OSA. The frequency of failed examinations and a comparison of cost analysis between complete polysomnography were described. Results: 41 exams lost at least one sensor. The sensor with the highest number of losses was the oximetry, observed in 14.28%. The 100 valid sleep studies allowed the diagnosis of severe OSA in 36 children. Sleep study accounts for approximately 63% of the value of the PSG type I, thus, it showed to be cost effective even with the repetition of the failed one. Conclusion: Sleep study (type III) may have high failure rates and it was a reliable exam for the identification of severe OSA. The cost analysis showed economic feasibility, even with a high failure rate and necessity of repetition.